2021
DOI: 10.3389/fendo.2021.785050
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages: New Horizons for Pituitary Adenoma Researches

Abstract: Macrophages are one of the most common infiltrating immune cells and an essential component of tumor microenvironment. Macrophages and the soluble cytokines and chemokines produced play an important role in tumorigenesis, progression, invasion and metastasis in solid tumors. Despite the multiple studies in other solid tumors, there is little known about macrophages in pituitary adenomas. Recently, studies about pituitary adenoma-infiltrated macrophages have been emerging, including the immunohistochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 84 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…Growing evidence has suggested that immune cells, particularly macrophages, play an essential role in the development and progression of pituitary adenomas [ 21 , 22 ]. Macrophages are present in both normal pituitary and PitNETs, and their types and populations vary depending on the subtype of PitNETs [ 23 25 ]. M2 macrophages are prevalent in the pituitary gland and may play a role in tumorigenesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has suggested that immune cells, particularly macrophages, play an essential role in the development and progression of pituitary adenomas [ 21 , 22 ]. Macrophages are present in both normal pituitary and PitNETs, and their types and populations vary depending on the subtype of PitNETs [ 23 25 ]. M2 macrophages are prevalent in the pituitary gland and may play a role in tumorigenesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary adenoma is the second most common intracranial tumor, with an incidence of 15% ( 1 ). Although they are benign, nearly 35–40% of pituitary adenomas are invasive ( 2 , 3 ). These adenomas are large; invade the cavernous sinus, sphenoid sinus, and clivus; are prone to recurrence after surgery; and are resistant to conventional treatments, resulting in a more difficult treatment regimen ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%